Airway injury from transoral endoscopic thyroidectomy vestibular approach. Issue 2 (3rd November 2021) - Long, Sallie M.; Ali, Khalid; Tufano, Ralph P.; Banuchi, Victoria E.
Abstract: Background: The transoral endoscopic thyroidectomy vestibular approach (TOETVA) is a novel technique that eliminates a cervical scar. This procedure carries unique risks, and data on outcomes are needed as more cases are performed. Methods: We describe two cases of airway injury during the TOETVA. A description of the procedure and management of the injuries is outlined. Results: In one case, a 3‐mm injury in the thyrohyoid membrane was identified. The TOETVA was converted to an open approach due to significant inflammation in the setting of Graves' and the repair was performed while open. In the second case, a fracture occurred from the thyroid notch to Broyle's ligament without avulsion. A primary repair was endoscopically performed. Conclusions: Airway injury is a possible complication of both open thyroidectomy and TOETVA. For TOETVA, trauma is most likely to occur in the midline during Hegar dilation and trocar placement through the central incision.